Ethanol Exposure Up-Regulates PD-L1/PD-1 Immune Checkpoint Pathway and Promotes Mammary Tumor Development - Xu, Wenhua; Wu, Linqing; Xu, Mei; Luo, Jia; Chen, Gang (Frontiers in Oncology, 2022)
Alcohol consumption in women enhances breast cancer incidence and ethanol is the main causal factor. Compromised host immunity through immunosuppression facilitates the development of many types of cancer, including breast cancer. Immune cells in breast tissues, particularly tumor-infiltrating CD8 cytotoxic T cells, play a critical role in the host anti-tumor immunity against breast tumorigenesis. These cytotoxic T cells are the major immune cells to carry out anti-tumor immunity through their cytotoxic effector function, which can be regulated by immune checkpoint pathways. The PD-1/PD-L1 pathway (the interaction between programmed death-1, PD-1, and its ligand, programmed death-ligand 1, PD-L1) is the best characterized one. However, the effects of ethanol exposure on T cell anti-tumor immunity and how that may contribute to ethanol-enhanced mammary tumorigenicity remain unknown. FVB.Cg-Tg(Wnt1)1Hev/J transgenic mice develop spontaneous mammary tumors starting around the age of 2-3 months and have been a widely-used mouse model for breast cancer research. Using this mouse model, the current study determined the effects of ethanol on the PD-L1/PD-1 pathway and how that may contribute to mammary tumorigenesis. The results indicated that ethanol exposure enhanced mammary tumor formation accompanied with an up-regulation of PD-1/PD-L1 pathway (increased PD-L1 levels in tumor tissue cells and the amount of PD-1-expressing tumor-infiltrating CD8 T cells) and inhibited T cell anti-tumor function, while inhibition of PD-1/PD-L1 restored T cell anti-tumor effector function and mitigated ethanol-enhanced tumorigenesis.